Circadian entrainment to red-light Zeitgebers and action spectrum for entrainment in the jewel wasp Nasonia vitripennis - Yifan Wang; Lijing Jin; Gregor Belušič; Leo W. Beukeboom; Bregje Wertheim; Roelof A. Hut (Journal of Comparative Physiology A, 2024)
Light is the most important environmental cue for the circadian system of most organisms to stay synchronized to daily environmental changes. Like many other insects, the wasp Nasonia vitripennis has trichromatic compound eye-based colour vision and is sensitive to the light spectrum ranging from UV to green. We recently described a red-sensitive, ocelli-based photoreceptor, but its contribution to circadian entrainment remains unclear. In this study, we investigated the possibility of Nasonia circadian light entrainment under long-wavelength red LED light–dark cycles and characterized the strength of red light as a potential Zeitgeber . Additionally, we measured the possibility of entrainment under various light intensities (from 5·10 12 to 4·10 15 photons·cm −2 ·s −1 ) and a broader range of wavelengths (455—656 nm) to construct corresponding action spectra for characterizing all circadian photoreceptors involved in photic entrainment. We also conducted electroretinogram (ERG) recordings for each wavelength in the compound eyes. Our findings demonstrate that Nasonia can entrain under red light dark cycles, and the sensory pathway underlying the red-light Zeitgeber response may reside in the ocelli. Combined with findings from previous research, we pose that blue- and green-sensitive rhodopsin photoreceptor cells function as the major circadian photoreceptors in both circadian entrainment by light–dark cycles and circadian phase shifts by light pulses, whereas the red-sensitive photoreceptor cell requires higher light intensity for its role in circadian entrainment by light–dark cycles.

Experimental evaluation of an indirectly-irradiated packed-bed solar thermochemical reactor for calcination–carbonation chemical looping - Lifeng Li; Alireza Rahbari; Mahdiar Taheri; Roelof Pottas; Bo Wang; Morteza Hangi; Leanne Matthews; Lindsey Yue; José Zapata; Peter Kreider; Alicia Bayon; Chi-Hwa Wang; et al. (Chemical Engineering Journal, 2023)

Mutations in the heparan sulfate backbone elongating enzymes EXT1 and EXT2 have no major effect on endothelial glycocalyx and the glomerular filtration barrier - Ramzi Khalil; Margien G. S. Boels; A. Bezuijen; J. E. Boers; P. C. de Bruin; M. A. A. M. van Dijk; P. Drillenburg; A. F. Hamel; H. M. Hazelbag; G. N. Jonges; R. E. Kibbelaar; K. H. Lam; et al. (Molecular Genetics and Genomics, 2022)
In this study, the effect of heterozygous germline mutations in the heparan sulfate (HS) glycosaminoglycan chain co-polymerases EXT1 and EXT2 on glomerular barrier function and the endothelial glycocalyx in humans is investigated. Heparan sulfate (HS) glycosaminoglycans are deemed essential to the glomerular filtration barrier, including the glomerular endothelial glycocalyx. Animal studies have shown that loss of HS results in a thinner glycocalyx. Also, decreased glomerular HS expression is observed in various proteinuric renal diseases in humans. A case report of a patient with an EXT1 mutation indicated that this could result in a specific renal phenotype. This patient suffered from multiple osteochondromas, an autosomal dominant disease caused by mono-allelic germline mutations in the EXT1 or EXT2 gene. These studies imply that HS is indeed essential to the glomerular filtration barrier. However, loss of HS did not lead to proteinuria in various animal models. We demonstrate that multiple osteochondroma patients do not have more microalbuminuria or altered glycocalyx properties compared to age-matched controls ( n = 19). A search for all Dutch patients registered with both osteochondroma and kidney biopsy ( n = 39) showed that an EXT1 or EXT2 mutation does not necessarily lead to specific glomerular morphological phenotypic changes. In conclusion, this study shows that a heterozygous mutation in the HS backbone elongating enzymes EXT1 and EXT2 in humans does not result in (micro)albuminuria, a specific renal phenotype or changes to the endothelial glycocalyx, adding to the growing knowledge on the role of EXT1 and EXT2 genes in pathophysiology.

The Risk of QTc-Interval Prolongation in Breast Cancer Patients Treated with Tamoxifen in Combination with Serotonin Reuptake Inhibitors - Koen G. A. M. Hussaarts; Florine A. Berger; Lisette Binkhorst; Esther Oomen - de Hoop; Roelof W. F. van Leeuwen; Robbert J. van Alphen; Daniëlle Mathijssen - van Stein; Natasja M. S. de Groot; Ron H. J. Mathijssen; Teun van Gelder (Pharmaceutical Research, 2020)
Purpose Antidepressants like the serotonin reuptake inhibitors (SRIs) are often used concomitantly with tamoxifen (e.g. for treatment of depression). This may lead to an additional prolongation of the QTc-interval, with an increased risk of cardiac side effects. Therefore we investigated whether there is a drug-drug interaction between tamoxifen and SRIs resulting in a prolonged QTc-interval. Methods Electrocardiograms (ECGs) of 100 patients were collected at steady state tamoxifen treatment, with or without concomitant SRI co-medication. QTc-interval was manually measured and calculated using the Fridericia formula. Primary outcome was difference in QTc-interval between tamoxifen monotherapy and tamoxifen concomitantly with an SRI. Results The mean QTc-interval was 12.4 ms longer when tamoxifen was given concomitantly with an SRI (95% CI:1.8–23.1 ms; P = 0.023). Prolongation of the QTc-interval was particularly pronounced for paroxetine (17.2 ms; 95%CI:1.4–33.0 ms; P = 0.04), escitalopram (12.5 ms; 95%CI:4.4–20.6 ms; P < 0.01) and citalopram (20.7 ms; 95%CI:0.7–40.7 ms; P = 0.047), where other agents like venlafaxine did not seem to prolong the QTc-interval. None of the patients had a QTc-interval of >500 ms. Conclusions Concomitant use of tamoxifen and SRIs resulted in a significantly higher mean QTc-interval, which was especially the case for paroxetine, escitalopram and citalopram. When concomitant administration with an SRI is warranted venlafaxine is preferred.

Plasma-Derived Human C1-Esterase Inhibitor Does Not Prevent Mechanical Ventilation-Induced Pulmonary Complement Activation in a Rat Model of Streptococcus pneumoniae Pneumonia - F. M. de Beer; H. Aslami; J. Hoeksma; G. van Mierlo; D. Wouters; S. Zeerleder; J. J. T. H. Roelofs; N. P. Juffermans; M. J. Schultz; W. K. Lagrand (Cell Biochemistry and Biophysics, 2014)

Species pool versus site limitations of macrophytes in urban waters - K. Vermonden; R. S. E. W. Leuven; G. van der Velde; A. J. Hendriks; M. M. van Katwijk; J. G. M. Roelofs; E. C. H. E. T. Lucassen; O. Pedersen; K. Sand-Jensen (Aquatic Sciences, 2010)

Radiation hybrid map of the porcine genome comprising 2035 EST loci - Anette Rink; Katie Eyer; Benjamin Roelofs; Kimberly J. Priest; Kathleen J. Sharkey-Brockmeier; Sudkamon Lekhong; Elif K. Karajusuf; Jason Bang; Martine Yerle; Denis Milan; Wan-Sheng Liu; Craig W. Beattie (Mammalian Genome, 2006)

Biogeochemical Constraints on the Ecological Rehabilitation of Wetland Vegetation in River Floodplains - L. P. M. Lamers; R. Loeb; A. M. Antheunisse; M. Miletto; E. C. H. E. T. Lucassen; A. W. Boxman; A. J. P. Smolders; J. G. M. Roelofs (Hydrobiologia, 2006)

Late-Onset Common Cancers in a Kindred with an Arg213Gln TP53 Germline Mutation - Mariëlle W. G. Ruijs; Senno Verhoef; Gea Wigbout; Roelof Pruntel; Arno N. Floore; Daphne de Jong; Laura J. van ′t Veer; Fred H. Menko (Familial Cancer, 2006)

Case Study Part 2: Probabilistic Modelling of Long-term Effects of Pesticides on Individual Breeding Success in Birds and Mammals - W. ROELOFS; D.R. CROCKER; R.F. SHORE; D.R.J. MOORE; G.C. SMITH; H.R. AKCAKAYA; R.S. BENNETT; P.F. CHAPMAN; M. CLOOK; M. CRANE; I.C. DEWHURST; P.J. EDWARDS; et al. (Ecotoxicology, 2005)

Case Study Part 1: How to Calculate Appropriate Deterministic Long-Term Toxicity to Exposure Ratios (TERs) for Birds and Mammals - R.F. SHORE; D.R. CROCKER; H.R. AKCAKAYA; R.S. BENNETT; P.F. CHAPMAN; M. CLOOK; M. CRANE; I.C. DEWHURST; P.J. EDWARDS; A. FAIRBROTHER; S. FERSON; D. FISCHER; et al. (Ecotoxicology, 2005)

A Review of Interspecies Toxicity Extrapolation in Birds and Mammals and a Proposal for Long-term Toxicity Data - R. Luttik; P. Mineau; W. Roelofs (Ecotoxicology, 2005)

Methyl 2-(methylthio)benzoate: the unique sulfur-containing sex pheromone of Phyllophaga crinita - P. S. Robbins; R. L. Crocker; S. Nojima; B. D. Morris; W. L. Roelofs; M. G. Villani (The Science of Nature, 2003)

Unusual pheromone receptor neuron responses in heliothine moth antennae derived from inter-species imaginal disc transplantation - S. Ochieng; K. Poole; C. Linn; N. Vickers; W. Roelofs; T. Baker (Journal of Comparative Physiology A, 2003)

A first-generation EST RH comparative map of the porcine and human genome - Anette Rink; Elizabeth M. Santschi; Katie M. Eyer; Benjamin Roelofs; Markus Hess; Myra Godfrey; Elif K. Karajusuf; Martine Yerle; Denis Milan; Craig W. Beattie (Mammalian Genome, 2002)

Pheromone-blend discrimination by European corn borer moths with inter-race and inter-sex antennal transplants - C. Linn Jr; K. Poole; A. Zhang; W. Roelofs (Journal of Comparative Physiology A, 1999)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Influence of ethanol induction on the metabolic activation of genotoxic agents by isolated rat hepatocytes - J. M. Neis; B. W. J. te Brömmelstroet; P. J. L. van Gemert; H. M. J. Roelofs; P. Th. Henderson (Archives of Toxicology, 1985)